PENGARUH MEDIA POP-UP BOOK TERHADAP HASIL BELAJAR IPA KELAS V DI SD NEGERI 111 PIDOLI DOLOK - Annisa Putri Siregar; Rahmi Seri Hanida; Junita Irawati (EDU RESEARCH, 2024)
This paper aims to determine whether implementing pop-up book media has an influence on the learning outcomes of class V students at SD Negeri 111 Pidoli Dolok in science subjects. This research employs an experimental, quantitative approach. This study included a total of 28 students from class V. We collected data using test and questionnaire methods. We processed the obtained data using Microsoft Excel and SPSS version 25. Data was analysed using product moment. The results revealed that the use of pop-up book media significantly enhanced the learning outcomes of the experimental class, resulting in a score of 85. We reanalyzed the posttest results using a t test and the Sig results. The 2-tailed value of 0.000 is less than 0.05, indicating the rejection of H0 and the acceptance of Ha. Meanwhile, the results of the independent sample t-test showed that the tcount was greater than the ttable, namely 5.358 > 2.160. These findings suggest that the use of pop-up book media affects learning outcomes.